COMPARATIVE EVALUATION OF THREE SEROLOGICAL TESTS FOR HIV DETECTION IN HARIPUR, PAKISTAN - REHMAN , MU; ZAMAN , Z; SAJJAD , A; ALI , N; HAYAT , A; KHAN , I; RAMZAN , HS (Biological and Clinical Sciences Research Journal, 2023)
Since many years ago and with rapid population growth, the human immunodeficiency virus (HIV) has been acknowledged as a serious public health concern worldwide. However, there does not appear to be enough information available on the prevalence of HIV infection in Haripur, Pakistan, as a whole. The current study's goals were to assess the effectiveness of three different HIV screening methods and to ascertain the seroprevalence of HIV infection in Haripur, Pakistan, among the general population. An immunochromatographic test (ICT), enzyme-linked immunosorbent assay (ELISA), and reverse transcription polymerase chain reaction (RT-PCR) were used to test a total of 5370 blood samples for the presence of anti-HIV antibodies and HIV-RNA at the antiretroviral therapy (ART) center in Hayatabad Medical Complex (HMC), Haripur. 756 (14.07%) of the 5370 blood samples tested positive for ICT, 639 (11.89%) for ELISA, and 606 (11.28%) for RT-PCR. Males were more likely to have an active HIV infection than females, with 468 having it compared to 138 who did (7.14%). The age group of 01–10 years showed no signs of infection, whereas the age group of 21–30 years had the highest infection rate (237, or 16.80%). However, the HIV seroprevalence in the married population was 423 (13.83%), compared to 183 (7.91%) in the single population. ICT should not be used to detect anti-HIV antibodies, and RT-PCR instead of ELISA should be used to detect HIV RNA. In order to avoid this illness, medical care centers in rural regions should guarantee the availability of treatment and screening facilities against this virus.